Down‐Regulation of Rac GTPase‐Activating Protein OCRL1 Causes Aberrant Activation of Rac1 in Osteoarthritis Development. Issue 8 (28th July 2015) - Zhu, Shouan; Dai, Jun; Liu, Huanhuan; Cong, Xiaoxia; Chen, Yishan; Wu, Yan; Hu, Hu; Heng, Boon Chin; Ouyang, Hong Wei; Zhou, Yiting
<x xml:space="preserve">Abstract</x> Objective Chondrocyte hypertrophy and mineralization are considered to be important pathologic factors in osteoarthritis (OA). We previously reported that Rac1 was aberrantly activated to promote chondrocyte hypertrophy, mineralization, and expression of matrix metalloproteinase 13 and ADAMTS in OA. However, the underlying mechanism of aberrant Rac1 activation in OA is unclear. The present study was undertaken to identify the specific molecular regulator controlling Rac1 activity in OA, as well as to investigate its function in chondrocyte hypertrophy, mineralization, and OA development. Methods Expression levels of 28 upstream regulators of Rac1 activity, including 8 GTPase‐activating proteins (GAPs) and 20 guanine nucleotide exchange factors, in OA and normal cartilage were assessed by quantitative polymerase chain reaction. Chondrocytes were transduced with lentiviral vectors encoding OCRL1, GAP, non‐GAP, CA‐Rac1, and DN‐Rac1, either alone or in combination. Alkaline phosphatase staining was used as a marker of chondrocyte hypertrophy. Rac1 activity was analyzed by pulldown assay. Finally, OA was established in mice by surgical transection of the anterior cruciate ligament and cutting of the medial meniscus. The mice were injected intraarticularly with OCRL1‐encoding lentivirus, and whole joints were assessed histologically 6 weeks after surgery. Results OCRL1 was abundantly expressed in normal cartilage and was the only significantly down‐regulated RacGAP in OA cartilage. Overexpression of OCRL1 inhibited interleukin‐1β–induced Rac1 activity, chondrocyte hypertrophy, and expression of hypertrophy‐related genes. Conversely, knockdown of OCRL1 elevated Rac1 activity and promoted chondrocyte hypertrophy and mineralization. Further, OCRL1 modulated Rac1 activity via its GAP domain. Finally, intraarticular injection of OCRL1‐encoding lentivirus protected against destruction and degeneration of cartilage in the mouse OA model. Conclusion OCRL1 acts as a RacGAP in cartilage to impede chondrocyte hypertrophy and OA development through modulating Rac1 activity. This regulatory pathway might provide potential targets for the development of new therapies for OA.